2018
DOI: 10.3389/fphar.2018.00465
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Uses, Pharmacological Efficacy, and Phytochemistry of Moringa peregrina (Forssk.) Fiori. —A Review

Abstract: Moringa is a sole genus of Moringaceae family with 13 species distributed in the tropical and sub-tropical regions. Among them, Moringa peregrina is one of the species which has wide range of traditional, nutritional, industrial, and medicinal values. The plant parts are used in folk medicine for many human health care purposes including diabetes, wound healing, disinfectant, fever, constipation, muscle pains, slimness, burns, labor pain, hypertension, malaria, stomach disorder, asthma, skin problems, and to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 108 publications
(128 reference statements)
0
53
0
Order By: Relevance
“…Moringa (mainly its leaves and fruits) has always been an integral part of people's diet. Additionally, Moringa leaves were fed to the ancient Mauryan warriors of India to provide them with energy and relieve their pain (2). Moringa peregrina (M. peregrina) is a drought-resistant tree that grows in the dry or semi-arid countries located near the Red Sea such as Somalia, Syria, Palestine, and Yemen (3).…”
mentioning
confidence: 99%
“…Moringa (mainly its leaves and fruits) has always been an integral part of people's diet. Additionally, Moringa leaves were fed to the ancient Mauryan warriors of India to provide them with energy and relieve their pain (2). Moringa peregrina (M. peregrina) is a drought-resistant tree that grows in the dry or semi-arid countries located near the Red Sea such as Somalia, Syria, Palestine, and Yemen (3).…”
mentioning
confidence: 99%
“…It was also observed that solvent system, for example, EA:DCE system, having more polarity had better antifungal and antimicrobial activity in comparison to the less polar solvent system, for example, DCM. The higher antimicrobial activity of the EA:DCM and EA:DCE solvent system might be because of the presence of steroids and terpenoids, which are absent in other solvent systems 14 (Table 2). Another possibility of this result is that the extracts of the more polar solvent system might be having more number chemical constituents, which attribute to the higher antimicrobial activity of the extracts of the more polar solvent systems 11 .…”
Section: Resultsmentioning
confidence: 99%
“…Fiori (Family: Moringaceae) is reported to possess a wide variety of biological activities that include antioxidant property, antimicrobial property, antidiabetic property, antispasmodic property, hepatoprotective property, antihypertensive property, lipid-lowering activity, anti-inflammatory activity, treatment of the mental disorders, and anticancer activity [11][12][13][14] . The complete plant description, its cultivation, the economic status, the different phytoconstituents, and the biological activity profile of the different solvent extracts of Moringa peregrina has also been disclosed in the published review articles 14,15 . According to one citation of 2018, most of the antimicrobial activity reports of the leaves of M. peregrina are related to the water-miscible solvents extracts and the compounds isolated from these extracts 14 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations